First Report of Accumulation of Lyngbyatoxin-A in Edible Shellfish in Aotearoa New Zealand from Marine Benthic Cyanobacteria - Laura Biessy; Jonathan Puddick; Susanna A. Wood; Andrew I. Selwood; Megan Carbines; Kirsty F. Smith (Toxins)
This study reports the first documented accumulation of lyngbyatoxin-a (LTA), a cyanotoxin produced by marine benthic cyanobacteria, in edible shellfish in Aotearoa New Zealand. The study investigates two bloom events in 2022 and 2023 on Waiheke Island, where hundreds of tonnes of marine benthic cyanobacterial mats (mBCMs) washed ashore each summer. Genetic analysis identified the cyanobacterium responsible for the blooms as Okeania sp., a genus typically found in tropical marine ecosystems. Analysis by liquid chromatography–tandem mass spectrometry indicated that the cyanobacteria produced a potent dermatoxin, lyngbyatoxin-a (LTA), and that LTA had accumulated in marine snails, rock oysters and cockles collected near the mats. Snails contained the highest levels of LTA (up to 10,500 µg kg−1). The study also demonstrated that the LTA concentration was stable in composted mats for several months. The presence of LTA in edible species and its stability over time raise concerns about the potential health risks to humans consuming LTA-contaminated seafood. This underlines the need for further studies assessing the risks of human exposure to LTA through seafood consumption, particularly as climate change and eutrophication are expected to increase the frequency of mBCM blooms. The study highlights the need to develop public health risk management strategies for mBCMs.